2021
DOI: 10.1111/aos.15008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of anti‐VEGF efficacy in diabetic macular oedema using intraocular cytokines and macular optical coherence tomography

Abstract: Purpose In eyes with diabetic macular oedema (DME), aqueous humour (AH) cytokine levels before and after anti‐vascular endothelial growth factor (VEGF) treatment were compared and correlated with optical coherence tomography structural parameters. Methods This prospective study included 56 control patients with cataracts and 83 patients with DME manifesting as diffuse retinal thickening (DRT), cystoid macular oedema and serous retinal detachment (SRD). AH samples were obtained before intravitreal injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is implicated in the pathogenesis of CNV, making intravitreal injection of anti-VEGF the first-line treatment ( 5 ). However, 15% of patients in our earlier study who had VEGF levels within the normal range were resistant to anti-VEGF medication ( 6 ). Aqueous humor (AH) concentration of VEGF was investigated as a therapeutic biomarker of anti-VEGF treatment efficacy ( 7 ) as it was strongly correlated with the concentration of VEGF in vitreous humor ( 8 ) which reflected the retinal microenvironment directly in normal axial eyes.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF) is implicated in the pathogenesis of CNV, making intravitreal injection of anti-VEGF the first-line treatment ( 5 ). However, 15% of patients in our earlier study who had VEGF levels within the normal range were resistant to anti-VEGF medication ( 6 ). Aqueous humor (AH) concentration of VEGF was investigated as a therapeutic biomarker of anti-VEGF treatment efficacy ( 7 ) as it was strongly correlated with the concentration of VEGF in vitreous humor ( 8 ) which reflected the retinal microenvironment directly in normal axial eyes.…”
Section: Introductionmentioning
confidence: 91%
“…AH and vitreous concentration of inflammatory cytokines, such as interleukin-8(IL-8), and monocyte chemotactic protein-1 (MCP-1), and interferon-inducible protein-10(IP-10), were significantly increased in CNV diseases ( 11 13 ). And these cytokines have been demonstrated to be mediators of inflammation and angiogenesis in various ocular and systemic diseases ( 12 ), which also induces VEGF upregulation while participating in the inflammatory response ( 6 ). Furthermore, pro-fibrotic cytokines which usually function additively or synergistically with inflammatory cytokines, were found to be significantly higher in HM eyes without CNV ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab, as a full-length (Fab and Fc) humanized murine IgG1 monoclonal antibody against VEGF-A, while Ranibizumab is a recombinant, humanized murine IgG1 monoclonal antibody fragment (Fab) targeting VEGF-A with higher affinity; Aflibercept is a recombinant fusion protein with VEGF receptors-1 and −2 fused to the Fc fragment of human IgG1; Similarly, conbercept is a recombinant fusion protein with high affinity for VEGF-A isoforms and PIGF; Brolucizumab is a single-chain antibody fragment targeting all forms of VEGF-A with higher solubility and lower molecular weight, allowing for administration of increased molar equivalents and in turn, may allow for longer intervals between doses. Though PDR and DME are two complications of diabetes mellitus and accumulating clinical and laboratory studies have evidenced the role of inflammation in the two complications, especially in DME ( Hillier et al, 2017 , 2018 ; Figueras-Roca et al, 2021 ; Hu et al, 2021 ; Mao et al, 2021 ; Minaker et al, 2021 ). However, studies assessing how the inflammatory cytokines and cytokines change after anti-VEGF therapy of DME have shown inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…The MCP-1 level in the aqueous humor of patients with RVO-ME was significantly higher compared with control and was positively correlated with the central retinal thickness ( 50 ). Diabetic ME patients with normal VEGF levels but with high levels of IL-8, IP-10, and MCP-1 showed more resistance to the anti-VEGF treatment ( 59 ). Our study showed significantly higher levels of ICAM-1 (no significance), VCAM-1, IP-10, and MCP-1 in AMD and RVO eyes, which are consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%